Satisfaction in Retail Sector Consumers: Consumer Perceptions of Service Quality and Price. - Rd Okky Satria; Anton Tirta Komara (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2020)
The provision of goods is one way to meet consumer needs. Excellent service quality and the applicating the affordable prices is one of the activities to achieve customer satisfaction. The purpose of this study is to determine the influence of service quality and price to customer satisfaction. The results reveal the problems regarding customer satisfaction with service quality and pricing. It is due to the lack of quality of services and the applied price. Therefore, it cannot increase customer satisfaction and decrease the level of consumers’ arrival. This research uses the questionnaire method with 100 respondents. The research applies verification analysis to analyze the data, consisting of multiple linear regression analysis and partial test (t-test) and simultaneous test (F-test). The results indicate that all independent variables as service quality and price, have a positive relationship. It is in line with the dependent variable, the consumer satisfaction. Hypothesis testing by using t-test shows two independent variables significantly affect consumer satisfaction. The F-test reveals these two variables affect customer satisfaction. The adjusted R-square of 0.620 indicates that the independent variable explains 62.0% service quality and price influence on customer satisfaction. The rest of 38.0% explain other variables outside the variables used in this research, such as promotion, distribution, value, and the others.